Identification of PTPN20 as an innate immunity-related gene in gastric cancer with Helicobacter pylori infection - Ma, Lianjun; Liu, Yang; Wang, Yizhao; Yang, Jiaxing; Lu, Jordan; Feng, Huijin; Ye, Shujun; Liu, Yanqing (Frontiers in Immunology, 2023)
Gastric cancer (GC) is among the severest diseases and causes lots of new incidences and deaths each year. Helicobacter pylori (Hp) is the major type of microbes colonizing in the stomach. These recent years, more and more evidence demonstrated that Hp infection is one of the main risk factors for GC. Elucidating the molecular mechanism about how Hp leads to GC will not only benefit the treatment of GC, but also boost the development of therapeutics for other gastric disorders caused by Hp infection. Here, we analyzed the differentially expressed, innate immunity-related genes in GC and revealed that protein tyrosine phosphatase non-receptor type 20 (PTPN20) is a significant prognostic marker in Hp-related GC. PTPN20 level could efficiently predict the survival of Hp-related GC patients. In addition, PTPN20 is associated with immune cell infiltration and tumor mutation burden in these GC patients. Moreover, PTPN20 related genes, the protein-protein interactions, and the ceRNA network of PTPN20 were also revealed. Our data suggest that PTPN20 may have critical functions in Hp-related GC. Targeting PTPN20 may be a promising way to treat Hp-related GC.